The natural history of internalizing behaviours from adolescence to emerging adulthood: findings from the Australian Temperament Project. Issue 13 (21st July 2016) - Betts, K. S.; Baker, P.; Alati, R.; McIntosh, J. E.; Macdonald, J. A.; Letcher, P.; Olsson, C. A.
Abstract : Background: The aims of the study were to describe the patterning and persistence of anxiety and depressive symptoms from adolescence to young adulthood and to examine long-term developmental relationships with earlier patterns of internalizing behaviours in childhood. Method: We used parallel processes latent growth curve modelling to build trajectories of internalizing from adolescence to adulthood, using seven waves of follow-ups (ages 11–27 years) from 1406 participants of the Australian Temperament Project. We then used latent factors to capture the stability of maternal reported child internalizing symptoms across three waves of early childhood follow-ups (ages 5, 7 and 9 years), and examined relationships among these patterns of symptoms across the three developmental periods, adjusting for gender and socio-economic status. Results: We observed strong continuity in depressive symptoms from adolescence to young adulthood. In contrast, adolescent anxiety was not persistent across the same period, nor was it related to later depressive symptoms. Anxiety was, however, related to non-specific stress in young adulthood, but only moderately so. Although childhood internalizing was related to adolescent and adult profiles, the associations were weak and indirect by adulthood, suggesting that other factors are important in the development of internalizing symptoms. Conclusions: Once established, adolescent depressive symptoms are not only strongly persistent, but also have the potential to differentiate into anxiety in young adulthood. Relationships with childhood internalizing symptoms are weak, suggesting that early adolescence may be an important period for targeted intervention, but also that further research into the childhood origins of internalizing behaviours is needed.